Mass cytometry detects H3.3K27M-specific vaccine responses in diffuse midline glioma - Sabine Mueller; Jared Taitt; Javier Villanueva-Meyer; Erin R. Bonner; Takahide Nejo; Rishi Lulla; Stewart Goldman; Anu Banerjee; Susan Chi; Nicholas Whipple; John R. Crawford; Karen Gauvain; et al. (2020)
BACKGROUNDPatients with diffuse midline gliomas (DMGs), including diffuse intrinsic pontine glioma (DIPG), have dismal outcomes. We previously described the H3.3K27M mutation as a shared neoantigen in HLA-A*02.01+, H3.3K27M+ DMGs. Within the Pacific Pediatric Neuro-Oncology Consortium, we assessed the safety and efficacy of an H3.3K27M-targeted peptide vaccine.METHODSNewly diagnosed patients, aged 3-21 years, with HLA-A*02.01+ and H3.3K27M+ status were enrolled in stratum A (DIPG) or stratum B (nonpontine DMG). Vaccine was administered in combination with polyinosinic-polycytidylic acid-poly-I-lysine carboxymethylcellulose (poly-ICLC) every 3 weeks for 8 cycles, followed by once every 6 weeks. Immunomonitoring and imaging were performed every 3 months. Imaging was centrally reviewed. Immunological responses were assessed in PBMCs using mass cytometry.RESULTSA total of 19 patients were enrolled in stratum A (median age,11 years) and 10 in stratum B (median age, 13 years). There were no grade-4 treatment-related adverse events (TRAEs). Injection site reaction was the most commonly reported TRAE. Overall survival (OS) at 12 months was 40% (95% CI, 22%-73%) for patients in stratum A and 39% (95% CI, 16%-93%) for patients in stratum B. The median OS was 16.1 months for patients who had an expansion of H3.3K27M-reactive CD8+ T cells compared with 9.8 months for their counterparts (P = 0.05). Patients with DIPG with below-median baseline levels of myeloid-derived suppressor cells had prolonged OS compared with their counterparts (P < 0.01). Immediate pretreatment dexamethasone administration was inversely associated with H3.3K27M-reactive CD8+ T cell responses.CONCLUSIONAdministration of the H3.3K27M-specific vaccine was well tolerated. Patients with H3.3K27M-specific CD8+ immunological responses demonstrated prolonged OS compared with nonresponders.TRIAL REGISTRATIONClinicalTrials.gov NCT02960230.FUNDINGThe V Foundation, the Pacific Pediatric Neuro-Oncology Consortium Foundation, the Pediatric Brain Tumor Foundation, the Mithil Prasad Foundation, the MCJ Amelior Foundation, the Anne and Jason Farber Foundation, Will Power Research Fund Inc., the Isabella Kerr Molina Foundation, the Parker Institute for Cancer Immunotherapy, and the National Institute of Neurological Disorders and Stroke (NINDS), NIH (R35NS105068).